Predictably irrational : the hidden forces that shape our decisions - Ariely, Dan. (London : HarperCollins, 2009)
An evaluation of the sources of illogical decisions explores the reasons why irrational thought often overcomes level-headed practices, offering insight into the structural patterns that cause people to make the same mistakes repeatedly.
1. The truth about relativity : why everything is relative, even when it shouldn't be -- 2. The fallacy of supply and demand : why the price of pearls, and everything else, is up in the air -- 3. The cost of zero cost : why we often pay too much when we pay nothing -- 4. The cost of social norms : why we are happy to do things, but not when we are paid to do them -- 5. The influence of arousal : why hot is much hotter than we realize -- 6. The problem of procrastination and self-control : why we can't make ourselves do what we want to do -- 7. The high price of ownership : why we overvalue what we have -- 8. Keeping doors open : why options distract us from our main objective -- 9. The effect of expectations : why the mind gets what it expects -- 10. The power of price : why a 50-cent aspirin can do what a penny aspirin can't -- 11. The context of our character, part I : why we are dishonest, and what we can do about it -- 12. The context of our character, part II : why dealing with cash makes us more honest -- 13. Beer and free lunches : what is behavioral economics, and where are the free lunches?
Includes bibliographical references (pages [341]-353) and index.
BIGD
Keywords: Decision making; Economics -- Psychological aspects; Consumer behavior; Decision making; Thought and thinking; Reasoning; Economics -- Psychological aspects; Consumers